Computational study on the role of residue Arg166 in alkaline phosphatases - Borosky, Gabriela Leonor (2017)
Quantum chemical calculations were performed with the goal of achieving a better understanding of the influence of Arg166 on the catalytic activity of alkaline phosphatases. The present results indicate that the active site Arg166 residue contributes to catalysis by orienting the phosphate monoester substrate in a favorable position for the rate-limiting nucleophilic attack. The stabilizing hydrogen bond interactions of the guanidinium group with two nonbridging oxygens of the phosphate decrease the barrier for the phosphoryl transfer process by attainment of a tighter and preorganized transition state.